Trends of Bacterial Pathogens and their Antimicrobial Susceptibility in Ocular Cultures - Sajjad, Mehwish (International Journal of Pathology, 2023)
Background: Eye infections caused by bacteria are a serious public health problem. These diseases, if not properly treated, can cause blindness and impaired vision. The study is designed to evaluate the bacterial etiologies and antimicrobial resistance profiles of the main pathogens involved in eye infections. Objectives: To isolate different pathogens from ocular culture and evaluate the antibiotic susceptibility pattern of these organisms Materials and Method: This was a retrospective study in which we retrieved the data of ocular cultures in Dow Diagnostic Reference and Research Laboratory, Dow University of Health Sciences from the period of 1stJanuary 2019 to 31stDecember 2021. All details including bacterial etiologies and antimicrobial susceptibility pattern were noted from the retrospective data. Results: During the study period, 44 patients were recruited who were requested by a physician for ocular cultures from the period of 1stJanuary 2019 to 31stDecember 2021. Most common bacterial isolate found is Streptococcus pneumonia followed by Staphylococcus aureus and Pseudomonas aeruginosa. In this study all bacterial isolate exhibited 100% susceptibility against chloramphenicol except Streptococcus pneumonia which is 94% susceptible. Streptococcus pneumonia had 100% resistance against Trimethoprim- sulfamethoxazole whereas 100% susceptibility against clarithromycin, linezolid and levofloxacin. Conclusion: Inference of study is that Coagulase Negative Staphylococcus was resistant to penicillin. This has a significant effect on the options of empirical management of ocular infections.